On Modalities with Possible Worlds - Ule, Andrej (Analiza: časopis za kritično misel, 2025)
I am discussing the concept of possible worlds as it is used in modal semantics, which Danilo Šuster also discusses in his book Modal Catapults. I wonder how to understand possible worlds in the talk of the non-existent, for example, in explicitly imaginary discourses. Only the context of the discussion, where modal propositions about virtual (irreal) entities or virtual (irreal) states of affairs appear but not a priori judgments about what is in principle logically possible or impossible, can establish a meaningful speech about relevant possible worlds. This raises several problems, e.g., interpreting statements that refer to both real and virtual entities, especially interpreting some counterfactuals about real and virtual entities. It seems that in some instances, we cannot “get rid” of counterfactuality, e.g., by semantic conversion into ordinary general sentences about possible worlds of a certain kind.